PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN MAHASISWA FAKULTAS EKONOMI ANGKATAN 2014-2016 UNIVERSITAS ISLAM MALANG - Fuji Santoso; Rois Arifin; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
AbstractThe purpose of this study is to know and analyze how the Influence ofService Quality And Facilities To Student Satisfaction Faculty of EconomicsAngakatan 2014-2016 Islamic University of Malang. The population in this studyis all students of the Faculty of Economics UNISMA. This research used surveymethod by taking sample from a population and using questionnaire as main datacollecting tool, with number 95 respondents. Analytical techniques in this studyusing multiple linear regression.The results showed that partially Variable Service Quality and Facilitieshave a positive and significant effect on Student Satisfaction. While simultaneously that Variable Service Quality and Facility Variable have positive and significanteffect to Student Satisfaction Variables.Keywords: Service Kuliah, Facilities, and Student Satisfaction